Problems and Guidelines for Error Correction of the Chinese Pronunciation of Thai Students: A Case Study of Chinese Language Competitions of the Schools under the Supervision of the Office of the Basic Education Commission - แก้วบุตร พิชัย; แก้วมณี ธีรพงศ์ (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
The objectives of this research were to study Thai students problems concerning the Chinese pronunciation and to offer the guidelines for error correction of Thai students in schools under the supervision of the office of the basic education commission. Researchers gathered data by investigating real time situations, using tape-records to record 250 competitors’ pronunciation all over in Thailand during the 2016–2017 academic years. Data were analyzed to find out the causes and factors affecting Thai students’ mispronunciation in Chinese language and offer recommendations for the correction concerning three aspects; (1) school’s policy on Chinese language instruction. (2) Chinese language teachers, and (3) Chinese language learners in order to find the appropriate methods in teaching Chinese pronunciation for Thai students. The main findings from 250 competitors showed that there were 389 errors which were from 2 main factors. The first factor is the internal factors including 1) Chinese consonant sound system, 2) Chinese vowel sound system, 3) Chinese tones, and 4) other problems. The second factor is external factors; 1) Chinese curriculum limitation 2) teachers limitation, and 3) students limitation. The results were collected and presented to show the most and the least frequent errors produced by Thai students.